THE EFFECT OF PERSONALITY, WORK MOTIVATION, AND COMPENSATION TO TURNOVER INTENTION - Agus Rinaldy; Parwoto, Parwoto (AGUSPATI Research Institute, 2021)
Abstract — This study aims to analyze the influence of personality, work motivation, and compensation on turnover intention. The population in this study were 297 employees of PT. MPI. The sample used is 75 employees, calculated based on the Slovin formula. Sampling method using Stratified Random Sampling. Methods of data collection using survey methods, with the research instrument is a questionnaire. Data analysis method using Partial Least Square 3.0 application. This study proves that personality has a negative and significant effect on turnover intention. Work motivation has a negative and significant effect on turnover intention. Compensation has a negative and significant effect turnover intention. Keywords - Personality, Work Motivation, Compensation, Turnover Intention